Analysis The Role Of Correctional Center (Bapas) The Exemption Conditional - Timbul Mangaratua Simbolon (Jurnal Daulat Hukum, 2018)
The problems of this study are 1) What is the role BAPAS of prisoners who have gained parole? 2) Any constraints faced by BAPAS in conducting guidance to inmates who obtain parole? The method used in this study using qualitative analysis, that takes into account the facts that exist in the field of practice which are then compared with the description obtained from the study of literature. From this analysis it can be seen the effectiveness of the criminal system that is instructive to the child as a criminal. Data obtained from both primary data and secondary data then analyzed qualitative diskritif troubleshooting procedures examined by exposing data have been obtained from the library studies and field studies were analyzed with the form of conclusions. The results using this sociological juridical methods conclude that: 1) Implementation guidance is felt still far from the expectations of the client, because the guidance conducted by the social counselor counsels are only just so monotonous at all. Whereas in the implementation of the Directive No. E-39-PR.05.03 of 1987 regarding Correctional Client Guidance was mentioned about the forms of activity, so that what has been a guide in the implementation of forms of activity can not run properly, 2).Constraints can be divided into two factors, namely the constraints caused by internal factors and constraints caused by external factors. As the constraints caused by the internal factor is the perception that the client to obtain a conditional release will apply to both the public, As for the problems caused by external factors is the client's premises much an obstacle for the client to do a report that it was his duty, so sometimes it is supervising the relevant social grant a dispensation for the client to do the report at a certain time.Keywords: Strategy; Correctional Centers (BAPAS) Non-Conditional.